A study on brand loyalty : empirical evidence from the mobile phone market in Malaysia - Linda, Seduram (2017)
Faced with a severe competitive business environment and the possibility of reaching maturity stage over the coming years, mobile phone brand owners are concerned about retaining and nurturing their profitable existing customers by strengthening customers’ brand loyalty. Surprisingly, studies relating to brand loyalty in the mobile phone setting are relatively scanty and much less studies have focused on comprehensive sets of brand loyalty determinants in the context of mobile phones. Therefore, understanding the formation of mobile phone brand loyalty is of utmost importance and it is the main concern of this study. Drawing upon Oliver’s four- stage loyalty model, this study investigated the relationship of utilitarian value and hedonic value (cognitive loyalty), brand satisfaction and emotional attachment (affective loyalty), brand trust (conative loyalty), and brand loyalty (action loyalty) sequentially. The study, moreover, examined the moderating effect of brand reputation in order to provide a clearer understanding of the mobile phone customers’ brand loyalty formation process. A total of 327 mobile phone users who resided in Klang Valley participated in the study. The results from the structural model supported the hypothesized paths: hedonic value influences brand satisfaction, hedonic value affects emotional attachment, brand satisfaction induces brand trust, emotional attachment influences brand trust, and brand trust influences brand loyalty. However, the hypothesized paths, i.e. utilitarian value influences brand satisfaction and utilitarian value influences emotional attachment, were not supported. The findings further indicated that the links of brand trust to brand loyalty are stronger when the brand has a high reputation, supporting the moderating effect of brand reputation. Finally, the implications are discussed, and the limitations of the study and future directions are briefly outlined.